Applying the Method of EOF Interpolation and 2dVar to Complete the Ocean Surface Current Data Obtained from HF Radar System - Thi Thu Mai, Nguyen; Sentchev, Alexei; Cuong, Tran Manh (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 1SDO - 10.25073/2588-1094/vnuees.4335, 2018)
Abstract : There are now over 350 high frequency radar (HF radar) stations operating on the coast of 37 countries around the world that allow the mapping of ocean surface current. However, observation from HF radars are often interrupted (loss of data) in both space and time due to signal inference, backscatters, and ocean state. In this study, we present a method to improve the surface current data collected from HF radar system. Firstly, the radial surface current data will be filtered intermittently, then the result is interpolated over time and space by the orthogonal experimental EOF and the 2dVar bi-directional variable interpolation. In addition, we have initially applied 2dVar interpolation method to the HF radar data in Vietnam and received initial positive results. The methods used in this paper promise to be effective when applied to improve surface flow data obtained from HF radar stations in Vietnam in the future. Keywords: EOF interpolation, 2dVar, Iroise sea, HF radar, ocean surface current. References: [1] Yaremchuk, M., and A. Sentchev, "A combined EOF/variational approach for mapping radar-derived sea surface currents," Cont. ShelfRes., pp. 31,758-768, 2011. [2] Shay, L. K., J. Martinez-Pedala, T. M. Cook, and B. K. Haus, "High-frequency radar mapping of surface currents using WERA," J. Am. Oceanic Tech., pp. 24,484-503, 2007. [3] Max Yarechuck, Alexei Sentchev, "Interpolation of the Radial Velocity Data from Coastal HF Radars," Naval Research Lab Stennis Detachment Stennis Space Center Ms Oceanography Div. ADA583326, 2013. [4] Richard E. Thomson, William J. Emery, Data Analysis Methods in Physical Oceanography, Third Edition, Elsevier Science, 2014. [5] N. O. o. R. a. Restoration, General NOAA oil spill modelling environment (GNOME) Technical Documentation.